Faktor Risiko Konsumsi Soft Drink dengan Kejadian Kegemukan pada Remaja di SMK Kristen Bala Keselamatan Palu - Faisal, Elvyrah; Anayanti, Ridha (Poltekkes Kemenkes Palu, 2021)
Adolescents are an age group that is prone to nutritional problems including obesity. Adolescent lifestyles that can trigger obesity include the consumption of soft drinks. The highest sweetener content in food and beverages is found in soft drinks, and it accounts for 12% of the total carbohydrate requirement which can trigger obesity. The purpose of this study was to determine the risk factors for soft drink consumption on the incidence of obesity in adolescents at the Vocational High School for Safety in Palu in 2018. This type of research used a case-control study. The sample in this study amounted to 64 people who were divided into 32 cases and 32 controls. A sampling of cases was carried out by the total population. Data collection techniques use digital scales and microtome to determine nutritional status, and the Semi-Quantitative Food Frequency Questionnaire form to determine the frequency and level of consumption of soft drinks. The analysis showed that the p-value for the frequency of soft drink consumption was 0.802 and the level for consumption of soft drinks was 0.297, with the OR value for the frequency of consumption of soft drinks = 1.485 and the OR value for the level of consumption = 1.98. The conclusion is that there is no relationship between the frequency of consumption of soft drinks, the level of consumption of soft drinks with the incidence of obesity in adolescents at the Vocational School of Salvation Army Palu. but have a risk respectively 1.485 times and 1.98 times the incidence of obesity. It is recommended that schools pay more attention to the types of drinks that are marketed in the school environment and teenagers are expected to be wiser in choosing snacks.